Implementasi Edukasi Ginjal Sehat Berbasis Sekolah untuk Meningkatkan Kesadaran Pencegahan Penyakit Ginjal Kronis - Lisa Fradisa; Kalpana Kartika; Salwana Salwana (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Chronic kidney disease (CKD) is a global health problem with a steadily increasing prevalence and is closely associated with lifestyle changes, including high salt and sugar intake, physical inactivity, and inadequate hydration habits. Early prevention is a crucial strategy to reduce the future burden of CKD, as health behaviors developed during childhood play a significant role in determining health status in adulthood. This community service activity aimed to improve the knowledge, attitudes, and awareness of elementary school students regarding kidney function, the importance of healthy lifestyle habits, and the introduction of metabolites as early indicators of kidney disorders. The method used was a school-based participatory education approach implemented through interactive lectures, visual media and educational videos, group discussions, quizzes, and educational games tailored to children’s characteristics. The activity was conducted with students of SDN 07 Kubu Gulai Bancah Bukittinggi. Evaluation was carried out through participation observation, question-and-answer sessions, and quizzes to assess students’ understanding before and after the intervention. The results showed an increase in knowledge and positive attitude changes regarding the importance of adequate water consumption, reducing high-salt foods and sugary drinks, and increasing physical activity. In addition, students demonstrated high enthusiasm for learning about metabolites as early signs of kidney disorders. School-based health education proved effective in instilling healthy lifestyle behaviors from an early age. This program is recommended to be integrated into ongoing school activities as a promotive and preventive strategy for CKD in the community.